Irrigation Water Use Efficiency in Olive Trees in Kairouan, Tunisia - Kamiyama, Hajime; Kefi, Mohamed; Kashiwagi, Kenichi (Asian Journal of Agriculture and Rural Development, 2021)
This study evaluated the technical efficiency and irrigation water use efficiency of olive farms in Tunisia, using Data Envelopment Analysis. In order to calibrate and validate the findings, data related to area, water use, water quality, cultivar, input, and yield were collected based on interviews from 45 irrigated olive farms in Kairouan Governorate. The results show that average input-oriented water use efficiency under the CRS and VRS specifications is 17.2% and 36.3%, respectively, indicating that the sampled olive farms could reduce the use of water by an average of 82.8% and 63.7% by improving the performance of irrigation systems. Also, it was found that there are large differences in irrigation water use efficiency between the CRS and VRS specifications. Consequently, this indicates that a number of olive farms can enhance overall efficiency by improving the scale of operation. In practical terms, this study provides significant insights for the olive growers in this study regarding the importance of removing scale inefficiency. Specifically, they need to consider the effects of water and soil quality on irrigated fields to improve the efficiency of irrigation water use.